A scanning electron microscope-based comparative evaluation of resin tag formation at the resin dentin inter-diffusion zone - Rhea Digholkar; Shalini Aggarwal; Shailendra Sonawane; Sharmika Chechare; Laxmikant Late; A.K. Anjali (Amaltea Medical Publishing House, 2023)
Aim of study was evaluate and compare the formation of the resin dentin interdiffusion zone (RDIZ) at the radicular dentin and resin interface after etching with phosphoric acid (PA) and glycolic acid (GA), using either light-cure and self-cured adhesives. Twenty extracted teeth were root canal treated. Post space preparation was done, and the samples were randomly divided into two main groups depending upon the etchant. Each group was further divided into two subgroups depending on the type of adhesive used. One group was etched with 37% PA (Prime® Dental Products PVT LTD, India) and the other with 35% GA (Glycolic 35 Peel, Rejsol, India). Etching was followed by the application of light-cured adhesive (3M ESPE Adper Single Bond, USA) or self-etch (3M ESPE Single Bond Universal, Germany). Fibre posts were then placed and after a coronal build-up, the teeth were sectioned longitudinally and observed under SEM. Statistical analysis: Data was analyzed by descriptive statistics as a percentage of resin tag density for all the groups. The Kruskall-Wallis test was applied for overall comparison and a Mann-Whitney U test for inter-group analysis. Resin tag density was found to be the highest in the coronal third followed by the middle third of radicular dentin and was the least in apical thirds for both groups. Resin tag density was similar for light cure and self-etch adhesives in the coronal, middle, and apical thirds of both groups. In conclusion this study concluded that GA could be thought of as a potential etchant for the radicular dentin.